AN ANALYSIS OF THE SPEECH ERRORS UTTERED IN HIHO KIDS YOUTUBE VIDEOS - Annisa Chairunnisa; Ahmad Talib; Muh. Tahir (JTechLP: Journal of Technology in Language Pedagogy, 2023)
This study aimed to find what types of speech errors uttered and investigate the dominant types of speech errors were uttered in HiHo Kids YouTube videos. This research approach was descriptive qualitative. The data sources in this study came from fifteen videos on HiHo Kids YouTube. Data were described based on the theory of Clark and Clark (1977). The results of the research showed that: (1) There were seven types of speech errors based on Clark and Clark’s theory. There were 98 speech errors uttered by 15 videos, consisting of 23 silent pauses, 27 filled pauses, 21 repeats, 1 retraced false start, 3 corrections, 2 stutters, and 21 interjections. (2) The most dominant error was filled pause, which consists of 27 utterances. Based on the results above, it can be concluded that speech errors uttered by the kids were normal because they did not use any script, they spoke spontaneously, and the listener can understand what the speaker said.